The Role of the Depok City Election Supervisory Board in Efforts to Prevent Money Politics Violations in the 2024 Legislative Election - Ria Febriyanti, Agnes; Fatkhuri, Fatkhuri (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Depok City is one of the areas that shows that there are still problems related to money politics. Urban Policy research through a survey of 800 respondents from 11 sub-districts in Depok City revealed that the vulnerability and threat of money politics and negative campaigns still tend to be high. This study aims to analyze the role of the Depok City Election Supervisory Agency (Bawaslu) in preventing money politics in the 2024 legislative election and highlight what factors hinder Bawaslu in preventing and handling money politics. This research uses institutional theory and the concept of participatory supervision to identify problems and findings in the prevention of money politics. The object of this study is the role and authority of the Depok City Bawaslu in taking action to prevent money political practices in the 2024 legislative election. The method used is a qualitative descriptive approach, with data collection techniques in the form of in-depth interviews and literature studies. The results of this study show that money politics still haunts the holding of the 2024 legislative elections caused by several factors, namely regulatory loopholes in legal subjects, limited regulations and authority of the Depok City Bawaslu, the community's persimive attitude towards the practice of money politics, and the Gakkumdu center which is still an obstacle to the performance of the Depok City Bawaslu. So to overcome this problem, a central role is needed for the Depok City Bawaslu as an election supervisory institution in preventing and handling election violations, especially money. The research emphasizes the detrimental impact of money politics on democracy, including its effects on representation, accountability, and the relationship between leaders and people. This research reveals that there are still challenges faced in implementation, such as regulatory gaps that need to be corrected and increased effectiveness in dealing with existing obstacles. This research highlights the importance of updating regulations related to money politics and increasing effectiveness in its implementation in the field.